Modeling of hydrogen production system for photovoltaic power generation and capacity optimization of energy storage system - Wei, Daohong; Li, Huawei; Ren, Yan; Yao, Xianhe; Wang, Long; Jin, Kunyong (Frontiers in Energy Research, 2022)
Hydrogen production using solar energy is an important way to obtain hydrogen energy. However, the inherent intermittent and random characteristics of solar energy reduce the efficiency of hydrogen production, so it is necessary to add an energy storage system to the solar power hydrogen production system. This paper establishes a model of photovoltaic power generation hydrogen system and optimizes the capacity configuration. Firstly, the system model is established by modeling and analyzing the mathematical model and using simulation software; secondly, the principle of optimal configuration of energy storage capacity is analyzed to determine the optimization strategy, and the storage capacity configuration algorithm based on the low-pass filtering principle is proposed, and the time constant is selected optimally; finally, a case study is conducted, whose photovoltaic installed capacity of 30MW, verifying the effectiveness of the proposed algorithm, and analyzing the relationship between energy storage capacity and smoothing effect. The results show that as the cut-off frequency decreases, the energy storage capacity increases and the smoothing effect is more obvious; and the proposed algorithm can effectively reduce the 1h maximum power variation of PV power generation. 0.078MW and 0.04MW respectively.